Differential physiological responses of a biogenic silver nanoparticle and its production matrix silver nitrate in Sorghum bicolor - Ziotti, Ana Beatriz Sicchieri [UNESP] (2021)
Silver nanoparticles (AgNP) have been extensively applied in different industrial areas, mainly due to their antibiotic properties. One of the environmental concerns with AgNP is its incorrect disposal, which might lead to severe environmental pollution. The interplay between AgNP and plants is receiving increasing attention. However, little is known regarding the phytotoxic effects of biogenic AgNP on terrestrial plants. This study aimed to compare the effects of a biogenic AgNP and AgNO3 in Sorghum bicolor seedlings. Seeds were germinated in increasing concentrations of a biogenic AgNP and AgNO3 (0, 10, 100, 500, and 1000 μM) in a growth chamber with controlled conditions. The establishment and development of the seedlings were evaluated for 15 days. Physiological and morpho-anatomical indicators of stress, enzymatic, and non-enzymatic antioxidants and photosynthetic yields were assessed. The results showed that both AgNP and AgNO3 disturbed germination and the establishment of sorghum seedlings. AgNO3 released more free Ag+ spontaneously compared to AgNP, promoting increased Ag+ toxicity. Furthermore, plants exposed to AgNP triggered more efficient protective mechanisms compared with plants exposed to AgNO3. Also, the topology and connectivity of the correlation-based networks were more impacted by the exposure of AgNO3 than AgNP. In conclusion, it is plausible to say that the biogenic AgNP is less toxic to sorghum than its matrix AgNO3.